Clinical and radiological factors predicting stroke outcome after successful mechanical intervention in anterior circulation. (30th March 2022) - Peisker, Tomáš; Vaško, Peter; Mikulenka, Petr; Lauer, David; Kožnar, Boris; Sulženko, Jakub; Roháč, Filip; Kučera, Dušan; Girsa, David; Kremeňová, Karin; Widimský, Petr; Štětkářová, Ivana
Abstract: The recanalization effect of large-vessel occlusion (LVO) in anterior circulation is well documented but only some patients benefit from endovascular treatment. We analysed clinical and radiological factors determining clinical outcome after successful mechanical intervention. We included 146 patients from the Prague 16 study enrolled from September 2012 to December 2020, who had initial CT/CTA examination and achieved good recanalization status after mechanical intervention (TICI 2b-3). One hundred and six (73%) patients achieved a good clinical outcome (modified Rankin Scale 0–2 in 3 months). It was associated with age, leptomeningeal collaterals (LC), onset to intervention time, ASPECTS, initial NIHSS, and leukoaraiosis (LA) in univariate analysis. The regression model identified good collateral status [odds ratio (OR) 5.00, 95% confidence interval (CI) 1.91–13.08], late thrombectomy (OR 0.24, 95% CI 0.09–0.65), LA (OR 0.44, 95% CI 0.19–1.00), ASPECTS (OR 1.45, 95% CI 1.08–1.95), and NIHSS score (OR 0.86, 95% CI 0.78–0.95) as independent outcome determinants. In the late thrombectomy subgroup, 14 out of 33 patients (42%) achieved a favourable clinical outcome, none of whom with poor collateral status. The presence of LC and absence of LA predicts a good outcome in acute stroke patients after successful recanalization of LVO in anterior circulation. Late thrombectomy was associated with higher rate of unfavourable clinical outcome. Nevertheless, collateral status in this subgroup was validated as a reliable selection criterion.